The Clinical Characteristics and Serological Outcomes of Infants With Confirmed or Suspected Congenital Syphilis in Shanghai, China: A Hospital-Based Study - Dai, Yi; Zhai, Guanpeng; Zhang, Shulian; Chen, Chao; Li, Zhihua; Shi, Wenjing (Frontiers in Pediatrics, 2022)
Background: Congenital syphilis (CS) is the infection of an infant or fetus with Treponema pallidum. The aim of this study was to investigate the clinical features and outcomes of serology reversion in infants diagnosed with confirmed or suspected congenital syphilis (CS). Methods: Infants admitted to the neonatology department of Children’s Hospital of Fudan University from 2013 to 2016 who met the case definition of CS or suspected CS were included in this study. Follow-up was performed in an outpatient clinic until reversion to nonreactivity of both toluidine red unheated serum test (TRUST) and Treponemal pallidum particle agglutination (TPPA). Follow-up data were collected until up to the end of 2019, when the last infant with CS reached 3 years of age. Results: In total, 682 infants were enrolled in this study, including 63 in the CS group and 619 in the suspected CS group. Forty-seven infants (74.6%) in the CS group had symptoms, and 57 (90.5%) had abnormal laboratory and/or long bone X-ray findings. By 6 months of age, TRUST results were negative in 53.3% of the infants with CS and in 100% of the infants with suspected CS. All the infants in the CS group returned to TRUST nonreactivity by 18 months of age. The TPPA results at 18 months of age showed that only 10.0% (3/30) of the patients in the CS group returned to nonreactivity, while a 99.6% (548/550) nonreactivity rate was observed in the suspected CS group. All the infants in the CS group returned to 19S-IgM-TPPA nonreactivity by 6 months of age. Conclusions: Although CS is an burdensome disease that may cause fetal and neonatal death, CS responds well to treatment when diagnosed and treated promptly, even when symptoms or lab/X-ray findings are present at birth.